Implementation of a body image program as a twisty country lane - Lorayne Robertson; Dianne Thomson; Wendy Barber (Journal of Teaching and Learning, 2013)
A teachers’ organization developed a grade-specific body image curriculum which was implemented in one Canadian province. The lessons were designed to promote body acceptance and to help students recognize and resist mediated constructions of ideal size and shape. One year after its introduction, a research study investigated the body image program’s implementation in six schools in different school districts. Data for the study include interviews with close to fifty teachers and surveys completed following the professional development sessions at the program’s introduction. The findings from this study indicate that, in addition to implementation factors such as resources, body image intervention programs at the school level are impacted by the complex ways in which bodies, including teachers’ bodies, are positioned socially. While the intent of the program was to provide a rich resource of materials for teachers, teachers needed more opportunities for reflection and support as they navigated new terrain. As a result, this particular curriculum implementation journey more closely resembled a road trip on a twisty country lane than one that took the shortest distance between two points.